HUBUNGAN PEKERJAAN IBU DENGAN PEMBERIAN ASI EKSKLUSIF DI WILAYAH KERJA PUSKESMAS AIRMADIDI KABUPATEN MINAHASA UTARA - Djue, Juwita; Tiwatu, Filia (Fakultas Keperawatan, Universitas Katolik De La Salle Manado, 2022)
Background:The low breastfeeding level can be a serious problem. This is due to the fact that mothers have occupation in factories or in offices which can take up a lot of time and they prefer to give formula milk to their babies. Objective: This study aimed to determine the relationship between employment and breastfeeding in the working area of Airmadidi Health Center, North Minahasa. Methods: This study used the quantitative method with the descriptive correlational design and the Cross-Sectional approach. The study was located is the Working Area of the Airmadidi Health Center, North Minahasa. The sampling was carried out using purposive sampling technique with n = 28 samples based on inclusion and exclusive criteria. This study used the non-parametric statistical test, the Spearman correlation test. Results: The results of data analysis using thetest There was a significant relationship between mothers' occupation and breastfeeding which obtained an r coefficient value of 0.382 indicating a fairly strong correlation with a p-value of 0.045 indicating a smaller value than the alpha significance value at <0.05. Conclusion: There is a significant relationship between mothers’ occupation and breastfeeding in the working area of Airmadidi Health Center, North Minahasa.